Quality-Improvement Initiative for Expedited Partner Therapy Provision in an Obstetrics and Gynecology Office. Issue 2 (6th August 2022) - Vasudeva, Isha; Hartnett, Janice; Bondi, Laura; Newmark, Alexis; Lindsay, Sarah
Abstract : A quality-improvement intervention including clinician education and workflow changes increases appropriate provision of expedited partner therapy. Abstract : OBJECTIVE: To perform a quality-improvement project to increase the rate at which expedited partner therapy is offered and prescribed at our clinic, in line with Connecticut Department of Public Health regulations. METHODS: We conducted quality-improvement interventions at an urban hospital-based outpatient clinic in Hartford, Connecticut, to improve prescribing of expedited partner therapy to at least 70% of eligible patients. We defined appropriate provision of expedited partner therapy by infection type (gonorrhea or chlamydia only per Centers for Disease Control and Prevention guidelines) and method of prescription per Connecticut Department of Public Health regulations (paper prescription or in-clinic dispensing). RESULTS: Rates of appropriate provision of expedited partner therapy improved with our interventions (21.6% vs 75.5%). We found an unexpected decrease in acceptance by patients after initiation of our interventions (81.3% vs 50.5%). CONCLUSION: We achieved our goal of improvement of rates of appropriate provision of expedited partner therapy to greater than 70% and have maintained this improvement over time. Future work should investigate potential barriers to expedited partner therapy acceptance, including type of infection, the effect of Department of Public Health regulation of prescribing options, and standard workflow in patient counseling.